THE ROLE OF EMOTIONAL INTELLIGENCE IN LEADERSHIP AND EMPLOYEE PERFORMANCE - Bajpai, Sharad Chandra; Mishra, Priyank (International Journal of Research -GRANTHAALAYAH, 2024)
A key component impacting the efficacy of leadership and performance of employees in contemporary administrations is emotional intelligence (EI). The effects of EI on leadership styles, employee output, contentment on the job, and interpersonal dynamics at work are the subject of this study. This research delves into the relationship between EI and successful decision-making, conflict resolution, and team cohesiveness by analysing the role of self-awareness, self-regulation, motivation, empathy, and social skills. Emotionally intelligent leadership is associated with increased employee engagement, decreased attrition, and overall organisational performance, according to this paper’s extensive literature assessment and empirical research. Leadership with high EI is associated with a more favourable work atmosphere, more innovation, and longer-term success, according to the research. At the end of the day, the research shows that EI training programs are necessary to boost leadership skills and company results.